Maintaining population health in low‐ and middle‐income countries during the COVID‐19 pandemic: Why we should be investing in Community Health Workers - Palafox, Benjamin (Archīum Ateneo, 2021)
Community health workers in low- and middle-income country primary health care systems are well suited to perform essential functions on the frontlines of Covid-19 pandemic responses. However, clear and coordinated guidance, updated infection control training, and reliable access to personal protective equipment must be ensured in order to deploy them safely and effectively. With these additional responsibilities, community health workers must also be supported to ensure that hard-fought gains in population health, including progress on non-communicable diseases, are sustained throughout the pandemic.